Tissue Expression of Carbonic Anhydrase IX Correlates to More Aggressive Phenotype of Basal Cell Carcinoma - Russo, Daniela; Varricchio, Silvia; Ilardi, Gennaro; Martino, Francesco; Di Crescenzo, Rosa Maria; Pignatiello, Sara; Scalvenzi, Massimiliano; Costa, Claudia; Mascolo, Massimo; Merolla, Francesco; Staibano, Stefania (Frontiers in Oncology, 2021)
Basal cell carcinoma (BCC) is the most common cancer in the white-skinned population accounting for about 15% of all neoplasms. Its incidence is increasing worldwide, at a rate of about 10% per year. BCC, although infrequently metastasizing, very often causes extensive tissue losses, due to the high propensity towards stromal infiltration, particularly in its dedifferentiated forms, with disfiguring and debilitating results. To date, there still is limited availability of therapeutic treatments alternative to surgery. We evaluated the immunohistochemical expression of the Carbonic Anhydrase IX (CAIX), one of the main markers of tissue hypoxia, in a set of 85 archived FFPE BCC tissues, including the main subtypes, with different clinical outcomes, to demonstrate a possible relationship between hypoxic phenotype and biological aggressiveness of these neoplasms. Our results showed that the expression level of the CAIX protein contributes to the stratification of BCC in the different risk classes for recurrence. We hypothesize for CAIX a potential therapeutic role as a target therapy in the treatment of more aggressive BCCs, thus providing an alternative to surgical and pharmacological therapy with Hedgehog inhibitors, a promising example of target therapy in BCCs.